COOPERATIVE LEARNING MANAGEMENT IN IBTIDAIYYAH MADRASAH - M. Khairul Amri (Roqooba Journal of Islamic Education Management, 2022)
One of the strategies and learning models is a cooperative learning strategy. Cooperative learning is a learning strategy that has recently received attention and is recommended by education experts to use. There are two reasons why cooperative learning is the choice, first, several research results prove that the use of cooperative learning can improve student achievement while at the same time increasing social relationship skills, fostering an attitude of acceptance of the shortcomings of self and others, and can increase self-esteem. Second, cooperative learning can realize students' needs in learning to think, solve problems, and integrate knowledge with skills. And these two reasons, then cooperative learning is a form of learning that can improve the learning system that has had weaknesses. In a good learning plan, a teacher must prepare carefully the learning scenarios that will be carried out in the class later. Starting from the goals and competencies that will or must be achieved in the meeting, certain methods and teaching aids needed, evaluations to be used and so on, so that with detailed preparation procedures will make a teacher really ready to teach.